'Short‐term treatment with methotrexate does not affect microvascular endothelial function in patients with psoriasis'. (21st February 2014) - Gyldenløve, M.; Jensen, P.; Løvendorf, M.B.; Zachariae, C.; Hansen, P.R.; Skov, L.
Abstract Background Psoriasis is associated with increased risk of cardiovascular disease (CVD), possibly due to chronic low‐grade systemic inflammation. Systemic anti‐inflammatory treatment might reduce the risk of CVD. Objective Our aim was to investigate if short‐term treatment with methotrexate influences microvascular endothelial function (MEF), an early surrogate marker of atherosclerosis, in patients with psoriasis. Methods We prospectively studied a hospital cohort of patients with psoriasis. Measurements of MEF were performed with the Endo‐PAT2000© device at baseline and after 8–10 weeks of treatment with methotrexate. At the same time points, we recorded anamnestic information, measured body mass index (BMI), waist and hip circumferences and blood pressure, and drew blood samples (lipid profile, HbA1 and hs‐CRP). Psoriasis severity was evaluated by psoriasis area and severity index (PASI) and the dermatology life quality index (DLQI). Results A total of 32 patients with psoriasis were included. Median age was 46 (range 18–82) years, and 50% were men. Twenty‐seven patients completed the study. After 8–10 weeks, median PASI had decreased significantly by 6.2 (from 9.8 to 3.6), and DLQI had decreased by 7 (from 9 to 2). No significant changes were observed in MEF, expressed by reactive hyperaemia index and augmentation index. Also, we saw no significant changes in BMI, waist–hip ratio, blood pressure and blood samples. Conclusion Short‐term treatment with methotrexate did not affect MEF in patients with psoriasis. Further studies are warranted.